PENEKANAN DIMENSI ORIENTASI PASAR PADA KINERJA PEMASARAN - Ade, Sinar Hubtriyan; NURHIDAYAH, EVINTA AMALIA; Ernawati, Fidyah Yuli; Linanjung, Yolanda Ardestya (JURNAL STIE SEMARANG, 2024)
Abstract. The research problems behind this research is the case of the decrease in income of outlet rent and store Semarang, beside that there is also gap of research about influence from market orientation to marketing performance. So this study aims to analyze the influence of customer orientation, competitor orientation and cross-functional coordination of marketing performance. The population in this research is all owner of rent and store outlet of Semarang, with sample number 100 respondents, taken based on purposive sampling method. Analyzer used is multiple linear regression. The results of this study proves empirically that customer orientation, competitor orientation and cross-functional coordination have positive and significant impact on marketing performance.